2017
DOI: 10.5005/jp-journals-10051-0137
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Microleakage of Zirconomer, Amalgomer CR, and Conventional Glass Ionomer (Type II) as Restorative Cements in Primary Teeth: An in vitro Study

Abstract: Scoring criteria: • 0 = No dye penetration • 1 = Dye penetration between the restoration and the tooth into enamel and dentin • 2 = Dye penetration between the restoration and the tooth in the enamel and dentin • 3 = Dye penetration between the restoration and the tooth into pulp chamber Results: The data were analyzed with nonparametric test (Kruskal-Wallis test; p < 0.005). There was no significant difference between the three restorative cements. The results showed that conventional GIC exhibited (type II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…evaluated the microleakage of Zirconomer, Amalgomer CR, and Conventional Glass Ionomer (type II) and found that Zirconomer had the highest microleakage in contrast to Amalgomer CR and Conventional Glass Ionomer type II. [ 11 ] According to the limitations of the current in vitro experiment, Hi-Dense outperformed Surefil and Zirconomer when used as a coronal barrier to microleakage in teeth that had undergone endodontic treatment. Compared with Hi-Dense, Zirconomer has less microleakage, whereas Surefil does.…”
Section: Discussionmentioning
confidence: 99%
“…evaluated the microleakage of Zirconomer, Amalgomer CR, and Conventional Glass Ionomer (type II) and found that Zirconomer had the highest microleakage in contrast to Amalgomer CR and Conventional Glass Ionomer type II. [ 11 ] According to the limitations of the current in vitro experiment, Hi-Dense outperformed Surefil and Zirconomer when used as a coronal barrier to microleakage in teeth that had undergone endodontic treatment. Compared with Hi-Dense, Zirconomer has less microleakage, whereas Surefil does.…”
Section: Discussionmentioning
confidence: 99%
“…The SEM analysis indicated voids and cracks on their surfaces. The voids may be incorporated during the sample preparation and cracks during the processing of samples for SEM analysis (125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136). The newest formula with 3% mass of Yttrium Trioxide Partially Stabilized Tetragonal Polycrystalline Zirconia (3YTZP) has been approved for use in dental clinic.…”
Section: Zirconia Glass Ionomer Cementmentioning
confidence: 99%